2016
DOI: 10.1007/s40263-016-0357-0
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Applications of Extended-Release Abuse-Deterrent Opioids

Abstract: Opioids are the mainstay for treatment of acute pain and cancer pain, and also have a role in the treatment of chronic non-malignant pain. There has been, however, a growing public health problem stemming from the misuse of opioid analgesics leading to serious consequences. To deter abuse, new formulations of extended-release opioid analgesics and tamper-resistant opioids have recently been developed. The concept of abuse-deterrent extended-release opioids is relatively new and, although abuse may not be compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 59 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…Additionally, they are designed to be slowly released into the body, thus reducing the potential for abuse. 72 Reports have shown that immediate-release tablets have been used recreationally and abused by injecting crushed tablets, some of which caused death. 73 As a result of data obtained from a US prescription drug-monitoring system, a study concluded that tapentadol has a significantly higher abuse potential than tramadol.…”
Section: Adverse Effects and Abuse Potentialmentioning
confidence: 99%
“…Additionally, they are designed to be slowly released into the body, thus reducing the potential for abuse. 72 Reports have shown that immediate-release tablets have been used recreationally and abused by injecting crushed tablets, some of which caused death. 73 As a result of data obtained from a US prescription drug-monitoring system, a study concluded that tapentadol has a significantly higher abuse potential than tramadol.…”
Section: Adverse Effects and Abuse Potentialmentioning
confidence: 99%